PENERAPAN SINGLE BAR SISTEM DALAM RANCANGAN UNDANG-UNDANG ADVOKAT PASCA PUTUSAN MAHKAMAH KONSTITUSI - Yolanda Veronika De La Brethoniere (JOURNAL EQUITABLE, 2023)
Referring to Article 28 paragraph (1) of the Advocate Law as the legal basis for the establishment of a single organization for the advocate profession named PERADI on December 21, 2004, the establishment of PERADI is a manifestation of a single bar association and has implications for the unification of the Indonesian advocate profession in a single organization for the advocate profession. only one, so that it is hoped that advocate organizations will become solid and can take part in improving the quality of advocates, curbing violations of the code of ethics for the advocate profession and eradicating judicial corruption. However, there are camps that disagree with the single bar, namely the Indonesian Advocates Congress (KAI) and the Association Indonesian Advocates (PERADIN) who approve of the multi bar system claim the multi bar system as an ideal system for Indonesian advocate organizations because it is considered in accordance with the mandate of Article 28E paragraph (3) of the 1945 Constitution, even though harmony and alignment are important for good competence for advocate organizations which has implications also to its members, this writing discusses the single bar post-judgment system of the supreme court and also provides input for the upcoming advocate